The Effectiveness of Nutrition Counseling using Leaflets and Videos to Increase Adolescents’ Knowledge About Fast Food at Dayah Jeumala Ama Lueng Putu Boarding School - Rara Miftahul Jannah Jannah; Teuku Jamni (JAND: Journal of Applied Nutrition and Dietetic, 2022)
Although boarding school students are already provided with food, they still prefer to eat fast food. However, the food provided for them are most likely low in fiber content and far from the word 'variety.' Therefore, counseling and nutrition education about the negative effects of fast food will significantly affect the development of adolescent knowledge. This study aims to analyze the effectiveness of nutrition counseling using leaflets and videos on increasing knowledge. This research is quantitative research with a quasi-experimental method. The population in this study was 62 teenagers. The sample collection in this study used the total sampling method. Pre- and post-test designs using a questionnaire were distributed to eighth-grade students. Data analysis was carried out using an independent t-test. Data are presented in tabular and textual forms. There is an increase in knowledge about the negative effects of fast-food using leaflet media, as evidenced by a p-value of 0.006. There is also an increase in counseling knowledge using video media, as evidenced by a p-value of 0.001. The average students’ knowledge about the negative effect of consuming fast food before counseling using leaflet media was 48.84; after counseling, it increased to 52.84. Meanwhile, counseling without the use of video media resulted in an average of 50.42, and it increased after counseling using video media to 54.58. Thus, it can be concluded that video media is more effective than leaflet media.